1999
DOI: 10.1002/hep.510290439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interferon Therapy on Hepatocellular Carcinogenesis in Patients With Chronic Hepatitis Type C: A Long–Term Observation Study of 1,643 Patients Using Statistical Bias Correction With Proportional Hazard Analysis

Abstract: The activity of interferon (IFN) is not elucidated from the viewpoint of cancer prevention in chronic hepatitis C patients en masse. The hepatocellular carcinogenesis rate was analyzed statistically in 1,643 patients with chronic hepatitis C: 1,191 patients with IFN therapy and 452 without IFN therapy. Hepatocellular carcinogenesis rates in the treated and untreated groups were 2.1% and 4.8% at the end of the 5th year, and 7.6% and 12.4% at the 10th year, respectively (P ‫؍‬ .0036). Multivariate analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
390
5
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(420 citation statements)
references
References 28 publications
21
390
5
4
Order By: Relevance
“…These events depend on various and numerous factors, including therapeutic management that can modify the natural course of the disease. As a matter of fact, active preventive procedures aiming to lower life-threatening complications have been carried out in this cohort such as digestive hemorraghe prevention by band ligation or interferon therapy which has been shown to improve survival and lower the risk of HCC incidence in patients with HCV-related cirrhosis [28,29] . As well, as regular HCC screening was carried out in our cohort, patients with small HCC underwent curative treatment, thus modifying their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These events depend on various and numerous factors, including therapeutic management that can modify the natural course of the disease. As a matter of fact, active preventive procedures aiming to lower life-threatening complications have been carried out in this cohort such as digestive hemorraghe prevention by band ligation or interferon therapy which has been shown to improve survival and lower the risk of HCC incidence in patients with HCV-related cirrhosis [28,29] . As well, as regular HCC screening was carried out in our cohort, patients with small HCC underwent curative treatment, thus modifying their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The elimination of HCV will prevent the progression of chronic hepatitis and associated complications 5. Several studies have reported that achievement of SVR results in the resolution of liver fibrosis6, 7 and a decreased incidence of HCC 8. However, development of HCC is sometimes seen even in patients who achieve SVR after DAA treatment, indicating the need for continuous surveillance for HCC after the eradication of HCV 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…2 Treatment with IFN-␣ decreases the incidence of HCC in patients with chronic hepatitis C with or without cirrhosis, especially in biologic or virologic responders. [3][4][5][6] Once HCC has developed, possible treatments include surgical resection, transcatheter arterial embolization and radiofrequency, ethanol, and microwave ablation. [7][8][9] However, the high rate of recurrence, which may be due to intrahepatic metastases and multicentric development, is an important clinical problem.…”
mentioning
confidence: 99%